National 'Clean Throat' Campaign (letter) - Corbett-Smith, Arthur, 1879-
1929-10 1929 1920s 1 page Primrose Hill 4091 A. CORBETT-SMITH (Major R.A.) 11 Glenilla Road Hampstead N.W.3 Corbetsŭ Hamp, London 27. X. 29. Dear Sir, This follows upon my telephone conversation of Saturday morning with your Representative. Will you be so good as to give to the two enclosed documents your consideration, reading the printed one first. Thereafter, I shall be glad if I may have a chat with you on the subject at the earliest possible moment, since the matter is urgent. I shall be happy to come down to see you. Or will you lunch with me within the next day or two — say, at the Savage Club? Perhaps you will be so good as to call me up in the morning upon your arrival and we could then doubtless arrange a meeting. With compliments, Very faithfully yours, A. Corbett-Smith J.B. Forbes Watson, Esquire Director The National Confederation of Employers' Organisations. 200/B/3/2/C693/3/13